1996
DOI: 10.1046/j.1365-2443.1996.900288.x
|View full text |Cite
|
Sign up to set email alerts
|

Otx1 function overlaps with Otx2 in development of mouse forebrain and midbrain

Abstract: Background: We previously reported that the homozygous mutation of Otx2 gene, a mouse cognate of the Drosophila head gap gene orthodenticle, causes failure in the development of the rostral head anterior to rhombomere 3, which may correspond to earlier Otx2 expression in cells destined for the anterior mesoendoderm. At the same time, the Otx2 heterozygous mutation displayed a phenotype characterized as otocephaly, probably related to expression in the anterior neuroectoderm at the subsequent pharyngula stage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 40 publications
1
32
0
2
Order By: Relevance
“…This suggests that Otx1 and Otx2 play synergistic roles in the development of several brain structures. It is worth noting the strong phenotypic variability of the double heterozogotes, in spite of the fact that the genetic background is strictly the same [48]. This is consistent with observations in humans.…”
Section: Interactions Between Loci: Non-allelic Non-complementationsupporting
confidence: 87%
“…This suggests that Otx1 and Otx2 play synergistic roles in the development of several brain structures. It is worth noting the strong phenotypic variability of the double heterozogotes, in spite of the fact that the genetic background is strictly the same [48]. This is consistent with observations in humans.…”
Section: Interactions Between Loci: Non-allelic Non-complementationsupporting
confidence: 87%
“…Furthermore, Otx1 +/-Otx2 +/-mutants are postnatally lethal, and Otx1 -/-Otx2 +/-phenotype could also not be examined. Otx1 -/-mutants do not exhibit marked defects in forebrain or midbrain development (Suda et al, 1996). These situations obscured the onset and the extent of cooperation between Otx1 and Otx2 in rostral brain development.…”
Section: Introductionmentioning
confidence: 99%
“…The results of analyses of Otx1 +/-Otx2 +/-mutants suggested that Otx2 and Otx1 cooperate in the regionalization of the rostral brain (Acampora et al, 1997;Suda et al, 1996;Suda et al, 2001). Owing to the occurrence of earlier visceral defects in Otx2 -/-mutants, however, this cooperation could not be examined in the Otx2 homozygous mutant state.…”
Section: Introductionmentioning
confidence: 99%
“…Proper regulation and function of this gene is crucial, as the mutation of Otx2 leads to defects in the rostral head in several developmental processes (Acampora et al, 1995;Acampora et al, 1997;Matsuo et al, 1995;Ang et al, 1996;Suda et al, 1996;Suda et al, 1997;Suda et al, 2001;Tian et al, 2002;Hide et al, 2002). However, very little is known about how Otx2 gene expression is dynamically regulated.…”
Section: Introductionmentioning
confidence: 99%